Assessing the Effectiveness of Arabic Language Learning During the Pandemic: A Case Study Of 9th Grade Students at Madrasah Tsanawiyah Al-Inayah Bandung City: Evaluasi Efektivitas Pembelajaran Bahasa Arab Selama Pandemi: Studi Kasus pada Siswa Kelas 3 di Madrasah Tsanawiyah Al-Inayah Kota Bandung - Arini Indah Syafitri; Nunung Nursyamsiah; Hikmah Maulani; Nalahuddin Saleh (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
This study examines the learning outcomes of Arabic language learning during and after the COVID-19 pandemic at Madrasah Tsanawiyah Al-Inayah in Bandung City, Indonesia. Qualitative research methods, including interviews, observations and documentation, were used to analyze the effectiveness of learning methods and factors influencing student learning outcomes. Purposive sampling was employed to select 15 ninth-grade students studying Arabic. The findings of the study reveal several important points. First, there were differences in the learning situation between home and school. Students must help understand Arabic material during online learning and catch up when returning to face-to-face classes. Second, students preferred to learn at school due to a more engaging and interactive environment, while online learning was associated with distractions and reduced motivation. Third, students perceived online methods as monotonous and less effective than post-pandemic methods. Fourth, various learning media were utilized during online learning. Additionally, students reported that even the online platforms couldn't help them study the Arabic language. The study emphasizes the importance of interactive and engaging methods to enhance student learning outcomes. The results contribute to a broader understanding of the impact of the COVID-19 pandemic on Education and provide valuable insights for educators and policymakers. Keywords: Arabic Language Learning, COVID-19, Post-Pandemic, Learning Outcomes Abstrak Studi ini menguji hasil belajar dalam pembelajaran bahasa Arab selama dan setelah pandemi COVID-19 di Madrasah Tsanawiyah Al-Inayah di Kota Bandung, Indonesia. Metode penelitian kualitatif, termasuk wawancara, observasi serta dokumentasi, digunakan untuk menganalisis efektivitas metode pembelajaran dan faktor-faktor yang memengaruhi hasil belajar siswa. Pengambilan sampel secara purposive dilakukan untuk memilih 15 siswa kelas 9 yang sedang mempelajari bahasa Arab. Temuan penelitian mengungkapkan beberapa poin penting. Yang pertama, terdapat perbedaan dalam situasi pembelajaran antara di rumah dan di sekolah. Siswa menghadapi kesulitan dalam memahami materi bahasa Arab selama pembelajaran daring dan kesulitan mengejar ketertinggalan ketika ke pembelajaran tatap muka. Kedua, siswa lebih memilih pembelajaran di sekolah karena lingkungan yang lebih menarik dan interaktif, sedangkan pembelajaran daring dikaitkan dengan gangguan dan motivasi yang menurun. Ketiga, siswa menganggap metode pembelajaran daring lebih monoton dan kurang efektif dibandingkan dengan metode pasca pandemi. Keempat, berbagai media pembelajaran digunakan selama pembelajaran daring, akan tetapi siswa mengaku bahwa platform daring pun tidak dapat membantu mereka dalam memahami pembelajaran bahasa Arab. Studi ini menekankan pentingnya metode yang interaktif dan menarik untuk meningkatkan hasil belaja siswa. Hasil penelitian ini berkontribusi pada pemahaman yang lebih luas tentang dampak pandemic COVID-19 pada penddikan dan memberikan wawasan berharga bagi pendidik dan pembuat kebijakan. Kata kunci: Pembelajaran Bahasa Arab, COVID-19, Pasca Pandemi, Hasil Belajar